Economic Geography of Investment Banking Since 2008: The Geography of Shrinkage and Shift. (8th August 2018) - Wójcik, Dariusz; Knight, Eric; O'Neill, Phillip; Pažitka, Vladimír
Abstract: Investment bank capitalism might have foundered during the global financial crisis in 2008, but what has happened to investment banks? Our analysis reveals that core investment banking activities have experienced a significant contraction, accompanied by diminished institutional and geographic concentration. Large banks have experienced the largest falls in revenue, and Asian banks have capitalized on the growth of their local capital markets. With direct access to the largest market in the world, US banks remain dominant globally, but their market shares have declined. Our results highlight the variegated nature of change under way in the global financial system, and its implications for geopolitics and geoeconomics.